FAKTOR YANG MEMPENGARUHI PENERAPAN GOOD COORPORATE GOVERNANCE - Tambunan, Marudut (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Article This research was conducted on companies listed in the Corporate Governance Perception Index report with the aim of analyzing the influence of company characteristics on Good Corporate Governance, which refers to research conducted by the former in Malasya. There are several differences between this study and the research conducted by Ariff et al, such as in determining the sample and the regression tool used. This research was conducted to analyze the characteristics of the company as a factor affecting the GCG rating. The characteristics of the company are divided into variables, namely profitability, concentration of ownership, company size, leverage and company growth. As the object in this article or this is part of the companies listed in the Corporate Governance Perception Index (CGPI) report for 2019 – 2021, and the sampling method in this study is the purposive sampling method. Based on the sample findings, a sample of 11 companies was obtained. The analysis technique used in the research in this article is multiple linear regression because the dependent variable in this study is data in the form of scores based on criteria determined by IICG. The results showed that concentration of ownership and company size had a significant positive effect on the GCG rating. The high percentage of ownership, Tobin's Q ratio and increase in total assets will get a higher CG score, while profitability, leverage, growth have no significant effect on the GCG rating.